Investigating Vague Language Expressions in EFL Students’ Debates in Higher Education - Muhamad Eginda Erlangga; Gilang Fadhilia Arvianti; Taufik Arochman (Universitas Tidar, 2025)
Debate serves as a vital method in English as a Foreign Language (EFL) learning, offering students a platform to enhance their speaking skills. However, EFL students often encounter challenges in debates, including the use of vague language. This study investigates the occurrence and patterns of vague language (VL) in EFL students’ debates, aiming to fill a gap in the literature regarding its impact in educational settings. Employing discourse analysis, data were collected from debate transcripts of 24 fourth- semester students at a public university in Central Java, Indonesia. The findings revealed 261 instances of vague language out of 9,317 words spoken, with vague possibility indicators being the most frequent (52.11%). While vague intensifiers and subjectivizer were present, they did not match the frequency of vague possibility indicators. The analysis illustrates the strategic importance of vague language in debates, despite its potential stemming from limited language proficiency. VL served various communication purposes: generalizing statements, navigating limited knowledge and proficiency, maintaining face wants and politeness, giving the right amount of information, saving time by simplifying communication, defending arguments confidently, being a rhetorical device, adding emotion, and helping to express complex ideas. Moreover, the study highlights the need to enhance both linguistic skills and strategic tactics among students to navigate complex debate scenarios effectively. The implications underscore the importance of addressing linguistic proficiency in EFL education, integrating explicit instruction on identifying and avoiding vague language, and fostering a culture of linguistic awareness in the classroom to promote effective communication skills among students.